2018
DOI: 10.1016/j.devcel.2018.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Human SEIPIN Binds Anionic Phospholipids

Abstract: Highlights d Human SEIPIN exists as an undecamer d The oligomerization state of SEIPIN is critical for its physiological function d The lumenal domain of SEIPIN forms an eight-stranded b sandwich fold d Both full-length SEIPIN and its lumenal domain bind anionic phospholipids

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
264
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(276 citation statements)
references
References 43 publications
11
264
0
1
Order By: Relevance
“…C) Alignment of Cdc50p and a monomer of human seipin (PDB 6DS5 44 ), a lipid binding protein illustrates the similar folds, although loops of Cdc50p are more extensive. The sequence identity between the two proteins is only 4%.…”
Section: Supplementary Data Figurementioning
confidence: 99%
“…C) Alignment of Cdc50p and a monomer of human seipin (PDB 6DS5 44 ), a lipid binding protein illustrates the similar folds, although loops of Cdc50p are more extensive. The sequence identity between the two proteins is only 4%.…”
Section: Supplementary Data Figurementioning
confidence: 99%
“…Importantly, the neutral and polar lipid constituents of adiposomes can be controlled as required for a particular experiment. For example, the role of protein-phospholipid binding in membrane targeting can be explored through manipulation of the adiposome phospholipid composition (Lemmon, 2008;Yan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The role of phosphatidic acid in LD protein targeting has been reported (Barneda et al, 2015;Yan et al, 2018), but the role of phosphatidyl inositol (PI), which is abundant on the LD, has attracted little attention (Bartz et al, 2007a;Tauchi-Sato et al, 2002). However, PI is known to be involved in protein binding in other contexts (Phan et al, 2016), so further investigation is well warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, seipin has been recently shown to mark the sites of LD formation 25 , and stand-alone deletion of seipin has been shown to lead to NL accumulation in the ER and delayed LD formation 26 . To test this hypothesis we first prepared a model of the transmembrane region of seipin based on the recently determined cryo-EM structures of the soluble part of seipin 27,28 and we embedded this model in a large membrane patch with 2% TG (Figure 4A,B). We next measured the concentration of TG molecules as a function of the distance from the protein complex, and we found that interactions between the TG molecules and the seipin complex raise the local concentration of TG in the proximity of the protein to 4%, twice the initial value in the bulk membrane ( Figure 4C,D) in our MD simulations.…”
mentioning
confidence: 99%
“…An elastic network, defined using MARTINI2 standard parameters for force constant and cutoffs, was used to keep the secondary structure of the helices. The position of the transmembrane helices was obtained from the coordinates of the terminal residues of the cryoEM structure of human Seipin, present in the PDB data bank with the code 6D5S27 . After a short 10 ps equilibration without restraints and subsequent 4 ns equilibration with positional restraint along all the directions (Fc=1000 kj/mol nm 2 ), positional restraints of Fc=1000 kj/mol nm 2 along…”
mentioning
confidence: 99%